ANALISIS PENGARUH INFLASI DAN INDEKS HARGA SAHAM GABUNGAN (IHSG) TERHADAP RETURN REKSA DANA SAHAM KONVENSIONAL ( Studi Pada Semua Reksa Dana Saham Konvensional Yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode Tahun 2013-2017) - Kamaria; Panjaitan, Fery; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
This is an undergraduate thesis prepared by Kamariah with a student identification number 130140064, entitled in the Indonesian language: "Analysis of the Influence of Inflation and the Composite Stock Price Index on Conventional Stock Refunds (Study on All Funds of Conventional Shares Registered in the Financial Services Authority) Period 2013-2017". This research was conducted from February to June 2018 in Pangkalpinang City. The purpose of this study is to determine the effect of Inflation and the Composite Stock Price Index to return mutual fund shares, either partially or simultaneously, on mutual fund products listed in the Financial Services Authority period 2013-2017. This study uses quantitative data analysis, multiple linear regression, and determination using secondary data. In the partial result using t-test, inflation has a negative effect on the return of mutual funds and stocks. While the composite stock price index has a positive effect on the return of equity funds. The results of this study also show that simultaneously using f test, inflation, and composite stock price index influence the return of equity funds. This is based on the calculation of 30.565 with Ftabel 19.00 means Fcount is greater than Ftable with 0,000 significance.